1992
DOI: 10.1128/jb.174.9.2891-2897.1992
|View full text |Cite
|
Sign up to set email alerts
|

The chloramphenicol acetyltransferase gene of Tn2424: a new breed of cat

Abstract: We have sequenced the gene coding for the chloramphenicol acetyltransferase of Tn2424 of plasmid NR79. This gene codes for a protein of 23,500 Da, and the derived protein sequence is similar to those of the chromosomal chloramphenicol acetyltransferases of Agrobacterium tumefaciens and Pseudomonas aeruginosa and of unidentified open reading frames, which may encode chloramphenicol acetyltransferases, adjacent to the ermG macrolide-lincosamide-streptogramin resistance gene of Bacillus sphaericus and the vgb vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 41 publications
1
69
2
Order By: Relevance
“…4), and these two proteins share 82.3% identity and 91.3% similarity. CATB3 also shares 67.4% identity (79.4% similarity) with CATB1, which was found in a Cm r isolate of A. tumefaciens and is not cassette determined (39), and 68.4% identity (84.4% similarity) with the product of an open reading frame (Ps orf) found in the chromosome of P. aeruginosa PAO1 (31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4), and these two proteins share 82.3% identity and 91.3% similarity. CATB3 also shares 67.4% identity (79.4% similarity) with CATB1, which was found in a Cm r isolate of A. tumefaciens and is not cassette determined (39), and 68.4% identity (84.4% similarity) with the product of an open reading frame (Ps orf) found in the chromosome of P. aeruginosa PAO1 (31).…”
Section: Resultsmentioning
confidence: 99%
“…2). This protein is a member of a recently identified family of CATs, here designated CATB proteins, that are not related to the majority of previously identified CATs (31,39). The new determinant, as the third identified member of this family, is designated CATB3 (catB3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NeuD shows significant similarity to a family of bacterial acetyltransferases that includes LacA and CysE of E. coli, NodL of Rhizobium leguminosarum (11), and the Tn2424 chloramphenicol acetyltransferase protein (24) (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…A BlastX search showed that the protein has homology to transacetylases from a Synechocystis sp. (68% similarity, 45% identity) (17), Enterococcus faecium satA (62% similarity, 40% identity) (29), A. tumefaciens cat (62% similarity, 40% identity) (43), Enterobacter aerogenes catB4 pBWH301 (61% similarity, 35% identity) (27), E. coli cat pNR79 (60% similarity, 38% identity) (27), and many other bacteria (Fig. 1).…”
Section: Isolation and Characterization Of The Mutant C58::a205mentioning
confidence: 99%